Kajian Etika Profesi Tentang Mutasi Pendeta di Jemaat GMIBM Bethesda Bangunan Wuwuk Wilayah Modayag - Lengkong, Syalomita Herlin; Sumakul, Henny W. B. (Educatio Christi, 2023)
Many researchers and theologians have discussed the profession of Pastor. However, discussing the ethics of priests in the context of their placement and treatment in a synod is still rare. This article aims to discuss the transfer of pastors in summary with their profession and priestly calling who received assignments from the church Synod at GMIBM Bethesda Gedung Wuwuk. The issue is whether the pastor who has been appointed also obeys the applicable regulations because they will have an impact on the ministry in the congregation. So, this problem has a tremendous impact on services and development. This research uses qualitative methods to support research, namely observation, interviews and literature study. The results of this research provide a deeper understanding of the priestly vocation which is also bound by the rules and regulations of the church, including the pastor. My thesis is that Pastors are also bound by regulations within the church organization, in this case the synod, where all applicable provisions and regulations must be obeyed.